MOLECULAR DOCKING STUDY ON 1H-(3,4d) PYRAZOLO-PYRIMIDINES AS CYCLIN DEPENDANT KINASE (CDK2) INHIBITORS - Phoujdar, Manisha S.; Aland, Gourishankar R. (International Journal of Current Pharmaceutical Research, 2016)
Objective: CDK2 inhibitors are implicated in several carcinomas viz. Carcinoma of lung, bladder, sarcomas and retinoblastoma. Pyrazolopyrimidines, being purine bioisosters inhibit more than one type of kinase. In this study, we are studying some novel derivatives of 1H-pyrazolo [3,4d] pyrimidines not reported earlier. The objective of the present study is an attempt towards design and development of 1H-[3,4-] pyrazolo-pyrimidines as CDK2 inhibitors through rational drug design. Methods: The present study has been done on CDK2 structure, PDB ID, 3WBL, co-crystallized with ligand PDY from RCSB protein data bank. A series of seventeen 1H-Pyrazolo [3,4-d] pyrimidines feasible for synthesis was docked on the said CDK2 receptor using Auto Dock 4 version, 1.5.6. Outputs were exported to discovery studio 3.5 client for visual inspection of the binding modes and interactions of the compounds with amino acid residues in the active sites. Results: The results of docking studies revealed that the present series of 1H-Pyrazolo[3,4-d] pyrimidines is showing significant binding through hydrogen bonding, hydrophobic, pi and Van der waals interactions, similar to the ligand PDY. Some conserved H-bond interactions comparable to bioisosters and compounds presently under human trials were noted. Ki values predicted in silico also suggest that the series will show promising CDK2 inhibitory activity. Conclusion: The series designed and docked can be further developed by synthesis and in vitro and in vivo activity. The receptor inhibitory activity can also be checked by specific receptor assays.